2007
DOI: 10.1007/bf02932118
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal period cytokines related to increased risk of future allergy development

Abstract: Testing of cytokine levels in colostrum, cord blood and amniotic fluid of healthy and allergic mothers and their newborns (using protein microarrays and quantitative analysis by ELISA) revealed differences in the levels of IL-5, IL-10, TGF-beta, TNF-alpha, EGF and eotaxin between healthy and allergic groups. Significantly higher concentration of IL-5 and IL-10 in the colostrum of allergic mothers and cord blood of their children and also tendency to a higher level of IL-4 found at allergic mothers and their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Cytokines detected in breast milk, include TGF-β, IL-10, IL-6, IL-1β, TNF, IFN-γ, IL-4, IL-5, IL-12, IL-13, G-CSF, GM-CSF, and M-CSF (Table 1) (63, 67, 68, 78, 79). Many of these cytokines have the potential to alter oral tolerance via their impact on the development of the infant's immune system and GIT (Figure 1).…”
Section: Cytokinesmentioning
confidence: 99%
“…Cytokines detected in breast milk, include TGF-β, IL-10, IL-6, IL-1β, TNF, IFN-γ, IL-4, IL-5, IL-12, IL-13, G-CSF, GM-CSF, and M-CSF (Table 1) (63, 67, 68, 78, 79). Many of these cytokines have the potential to alter oral tolerance via their impact on the development of the infant's immune system and GIT (Figure 1).…”
Section: Cytokinesmentioning
confidence: 99%
“…One cohort study generated two publications, and the results were summarized according to the study population, rather than by publication. Five studies were excluded as they did not assess any of the identified outcomes: one examined the effect of probiotic administration on the risk of eczema development and allergic sensitization only, without reporting the results on association with HM TGF‐β, two studies investigated TGF‐β in isolation from any allergic outcomes, and two studies assessed association between TGF‐β and immunological but not allergic outcomes in infants . Due to a limited number of studies reporting immunological outcomes, the scope of this systematic review is limited to allergic outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…This may be a consequence of a still active inflammatory reaction (Erbağci et al 2005 ). In milk from a mother with allergies, one can observe higher concentration of cytokines produced by lymphocytes Th2 (IL-4, IL-13, IL-5, IL-10) and lower TGF-β (Hrdý et al 2012 ; Prokesová et al 2006 ; Ragib et al 2009 ; Zizka et al 2007 ).…”
Section: Cytokines In Milkmentioning
confidence: 99%
“… Mizuno et al 2012 Subclinical mastitis N = 110 (56 from left breast and 54 form right breast collected from 44 healthy women) 25 cytokines IL-2, IL-2R, IL12p40/70, IL-15, IFN-α, IFN-γ, MIG, IP-10, IL-4,IL-5, IL-13,IL-7, IL-17, GMCSF, IL-10, EPO, IL-1RA, TNF-α, IL-6, IL-8, IL-1β, RANTES, EOTAXIN 2 • Factors associated with inflammation (e.g., TNF-α, IL-6, Il-8, IL-17) were significantly increased in SCM samples. • Only IL-4 from Th2 in higher concentrations in SCM samples • The Th1/Th2 ratio; predominant elevation of cytokines that belong to the Th1 –lymphocyte Tuaillon et al 2017 N = 108 Categorized as SCM (Na:K > 0.6); non-SCM (Na:K < 0.6) IL-1β IL-6 IL-8 TNF-α 3 • IL-8 and TNF-α where higher in SCM mothers (most notably in transitional milk) Li et al 2018 Allergy Colostrum milk (3 days after delivery) Allergic ( n = 15–44) and non-allergic mothers ( n = 15–64) IL-4, IL-6, IL-8, IL-10, _IL-12, IL-13, IFN-γ, TGF-β1, eotaxain, GRO-α, RANTES, TNF-α, EGF 1 • Cytokines present in colostrum with high quantities (mediana > 100 pg/mL): IL-4, IL-5, IL-10, IL-13, INF-γ, TGF-β, TNF-α, MCP-1, GRO-α, EGF • Colostrum form allergy mothers: IL-5, IL-10, and IL-4; higher levels compared to healthy mothers Zizka et al 2007 9 healthy mothers 11 allergic mothers IL-2, IL-4, IL-8, IL-10, IL-13, IFN-γ, TGF-β1, EGF 1,4 • Expression of IL-4, IL-13, and EGF was higher and levels of IFN-γ decreased in the colostral cells of allergic mothers compared to healthy. Hrdý et al 2012 13 allergic mothers 9 healthy mothers Colostrum (3 days) Mature milk (1 month) IL-10, TGF-β1 1 • TGF-β concentration had a significant difference between colostrum and mature milk in milk from allergy mothers.…”
Section: Cytokines In Milkmentioning
confidence: 99%
See 1 more Smart Citation